(The approach of Abu Al- Hassan Dairy Al- Din Al- Bayh qi (565AH- 1266CH) in his book Al- Kaman (Comparative analytical Study) (Journal of the College of Basic Education, 2024)
The Study dealt with many important narrations pertaining to various and different topics in terms of the historical periods of the historian Al- Bayh qi (565AH- 1266AD) who left us a great legacy in many aspects, as he was jurist at one time and a historian and a astronomers at another, TheEncyclopedia with which this historian was distinguished made him write a book that many have been devoid of ambiguity, that his name bore, present and located between the folds of books, absent and unknown in terms of his presence among the books of history.